Possible pathogenicity of commensal Entamoeba hartmanni revealed by molecular screening of healthy school children in Indonesia - Takahiro Matsumura; Joko Hendarto; Tetsushi Mizuno; Din Syafruddin; Hisao Yoshikawa; Makoto Matsubayashi; Taro Nishimura; Masaharu Tokoro (Tropical Medicine and Health, 2019)
Abstract Background Although parasites are still endemic in developing areas, residents in those regions seem not to be affected by the presence of intestinal protozoans. This study aimed to investigate whether pathogenic and commensal protozoans are the causal agents of diarrhea via a school-based cross-sectional survey conducted in Indonesia, in September 2016. Results Molecular screening for intestinal protozoans in collected 144 stool samples from healthy students (age range 7–15 years) was carried out. The prevalence of protozoan parasites was as follows: Giardia intestinalis (56.3%), Entamoeba histolytica (0%), E. dispar (6.9%), E. moshkovskii (0%), E. hartmanni (31.3%), and E. coli (44.4%). Observational evaluation of stool conditions using the Bristol stool chart confirmed the loose stool rate (33.3–90.9%) in each age group. Logistic regression analysis of protozoan infection or colonization for loose stool (mild to severe diarrhea) as an outcome revealed no significant findings in examined protozoans including pathogenic G. intestinalis infection [adjusted odds ratio (AOR) 0.78, 95% confidence interval (CI) 0.36–1.67], except in E. hartmanni colonization (AOR 2.81, 95% CI 1.1–3.7, P = 0.026). Conclusions The molecular survey of intestinal protozoans targeting healthy population with their stool form evaluation could address the pathogenicity of those parasites appropriately. In comparatively higher-age children at least 7 years of age or greater in the endemic area, G. intestinalis could regard commensal, while E. hartmanni seems to possess a certain pathogenicity as a causal agent of mild diarrhea.